2021
DOI: 10.1002/mame.202100464
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Tooling for Injection Molded Microfluidics

Abstract: Microfluidics have been used for several decades to conduct a wide range of research in chemistry and the life sciences. The reduced dimensions of these devices give them advantages over classical analysis techniques such as increased sensitivity, shorter analysis times, and lower reagent consumption. However, current manufacturing processes for microfluidic chips either limit them to materials with unwanted properties, or are not cost‐effective for rapid‐prototyping approaches. Here the authors show that inla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Typically, industrial production runs would be far longer, reaching hundreds of components. Convery et al [ 33 ] confirmed that an inlay of the same 3D‐printed material will not suffer significant degradation even after 500 parts are fabricated using the inlay for an injection molding run. They found that the micro‐channels in their designs were still within acceptable error margins even after 500 parts were produced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, industrial production runs would be far longer, reaching hundreds of components. Convery et al [ 33 ] confirmed that an inlay of the same 3D‐printed material will not suffer significant degradation even after 500 parts are fabricated using the inlay for an injection molding run. They found that the micro‐channels in their designs were still within acceptable error margins even after 500 parts were produced.…”
Section: Resultsmentioning
confidence: 99%
“…There are a significant number of variables that can influence the replication quality of the molding cycle including injection velocity, holding time and pressure, tooling temperature, etc. [20,32,33,36] These all have individual influence over the quality of replication; therefore, it would seem reasonable that the parameters will not have been optimally tuned to facilitate the best replication possible for these rough surface topographies. Non-optimum molding parameters can lead to incomplete filling of the mold and poor replication.…”
Section: Rough Surface Replication Studymentioning
confidence: 99%
“…Lee et al [ 146 ] discussed advantages and limitations of rapid injection molding and provided design recommendations to successfully utilize this method for microscale cell-based assay development. Convery et al [ 147 ] showed that inlays for injection molding could be three-dimensionally printed. Generally, the main drawbacks of microinjection molding are material restrictions related to thermoplastics and mold expensive fabrication and limited resolution [ 25 , 137 ].…”
Section: Fabrication Of Microfluidic Devicesmentioning
confidence: 99%
“…26 Furthermore, DM technologies could be employed in either direct writing mode to pattern fully functional devices directly on the substrate, or to create micromoulds for polymer casting in a similar way to soft lithography and injection moulding. 27 In this way, those groups experienced in soft lithography can incorporate all the advantages of DM direct writing modes while maintaining the option to make alternative micromoulds for PDMS casting (Fig. 2, interchange between master mould and DM stations).…”
Section: Digital Manufacturing: Giving Microfabrication Control To En...mentioning
confidence: 99%